Enhancing Students’ Self-Confidence In Mathematics Through Geogebra-Assisted TAPPS - Indri Lestari; Rina Oktaviyanthi; Tb. Sofwan Hadi; Nagina Slavina (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2026)
This study aimed to investigate the effectiveness of GeoGebra-assisted Thinking Aloud Pair Problem Solving (TAPPS) in improving students’ self-confidence in mathematics learning. The study employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The participants consisted of 70 eleventh-grade students from a public senior high school in Tangerang, Indonesia, selected through purposive sampling. The sample was divided into an experimental group and a control group, each consisting of 35 students. Data were collected using a self-confidence questionnaire comprising 30 statements based on four dimensions of self-confidence: belief in one’s own abilities, positive thinking and action, optimism and perseverance, and adaptability and social interaction. The data were analyzed using descriptive statistics, normality and homogeneity tests, an independent samples t-test, and N-gain analysis. The results revealed that the experimental group demonstrated greater improvement in self-confidence than the control group. Although the post-scale comparison did not indicate a statistically significant difference between groups (p = .060), the N-gain analysis showed a significant difference in improvement (p = .001). These findings suggest that GeoGebra-assisted TAPPS contributes positively to the development of students’ self-confidence and facilitates greater growth in confidence throughout the learning process. Therefore, the integration of collaborative problem-solving strategies and dynamic mathematical visualization can be considered a promising approach for promoting positive affective outcomes in mathematics learning